Oceanographic Conditions on Small Pelagic Fishery in the Gulf of Bone Waters (Torani Journal of Fisheries and Marine Science, 2018)
This study aimed to investigate the relationship between the dinamic oceanographic condition and fluctuation in the catch of small pelagic fish. Study on the dinamic oceanographic conditions were focused on the sea surface temperature (SST), chlorophyll-a concentration (SSC) and water depth. The study took place in the area of Gulf of Bone located, data collection was started from April to September 2017. The data were collected using experimental fishing metode (large liftnet) and applications of remote sensing in satellite oceanography, which then analysed using Geographic Information System (GIS) dan Generalized Additive Models (GAMs). The result showed that the distribution of small pelagic fish tends to be within the area of temperature ranging from 29.5 to 30.0oC, the chlorophyll-a from 0.7 to 0.9 mg.m-3 and concentrated within the coastal area with in waters depth maximum of 100 m.Keywords: Oceanography, small pelagic fish, distribution, fishing ground, Gulf of Bone